ALTERNATIF PENYELESAIAN SENGKETA WILAYAH LAUT INDONESIA-MALAYSIA - Satriyo Kusumo, Ayub Torry; Leksono, Handojo (Faculty of Law, Universitas Sebelas Maret, 2013)
AbstractThis study discusses alternative resolutions on maritime boundary dispute between Indonesia and Malay- sia. It was based on a legal research, which used statutes and case approach. The research materials were collected by literature study and analyzed by applying the interpretation analysis technique.The result shows that the alternative resolutions of Indonesia-Malaysia border dispute can be carried out through several mechanisms. First, by referring to the UNCLOS 1982, through Bilateral Mutual Agreement on drawing an equidistant line using the equity principle and considering relevant circumstances. Second, by means of ASEAN; and third, by means of International Court of Justice mechanism regarding the equitable principle and relevant circumstances.Keywords: the outermost islands, border management, maritime dispute settlement, archipelagic state ABSTRAKPenelitian ini membahas alternatif penyelesaian sengketa batas maritim antara Indonesia dan Malaysia. Kajian ini berdasarkan penelitian hukum dengan menggunakan pendekatan undang-undang dan pendekatan kasus. Pengumpulan bahan hukum melalui studi kepustakaan dan dianalisis dengan teknik analisis interpretasi hukum. Hasil pembahasan menunjukkan alternatif penyelesaian sengketa batas wilayah Indonesia-Malaysia dapat dilakukan dengan beberapa cara. Pertama, mengacu pada UNCLOS 1982 melalui Bilateral Mutual Agree- ment dalam menarik garis sementara yang menggunakan prinsip sama jarak dan mempertimbangkan faktor yang relevan, kedua, melalui mekanisme ASEAN, dan ketiga, melalui mekanisme Mahkamah Internasional dengan mengedepankan equitable principle dan relevant circumstances.Kata kunci : Pulau-pulau terluar, pengelolaan batas wilayah, penyelesaian sengketa maritim, negara kepulauan